ICT-Driven Knowledge Economy In Bangladesh: Issues And Constraints - Chowdhury, Mohammed S.; Alam, Zahurul (Journal of Knowledge Management Practice, 2009)
The paper reveals that the knowledge revolution, led by information and communication technology, lies at the heart of economic development of Bangladesh. The inability to access and use of ICT is a barrier to the creation of knowledge-based society in Bangladesh. The paper has identified that in order to create an ICT-driven knowledge society Bangladesh needs a knowledgeable workforce, government support and incentives, transparent and democratic institutions, innovativeness of the society, and a sound telecommunication infrastructure. The universities of the country need to be encouraged and adequately financed so that they can become the true abode of research and development - just like other universities in other parts of the world. In the area of communication technology, the competitiveness of the country in today’s information rich world will depend on its ability to access and exchange information both locally and globally.
Keywords: Information technology; Communication technology; Transparency; Knowledge economy; Hardware infrastructure; Software infrastructure; Innovation